Catalytic dehalogenation of hexachloroethane using vic-dioximes nickel complexes - Pizarro, Sebastian; Angel, Constanza; Araya, Michael; Delgadillo, Álvaro (Journal of the Chilean Chemical Society, 2024)
The electrochemical degradation of hexachloroethane using bis(dimethylglyoximato)nickel(II), [Ni(dmgH)2]; bis(diphenylglyoximato)nickel(II), [Ni(dpgH)2]; difluoroborylbis(dimethylglyoximato)nickel(II), [Ni(dmgBF2)2]; and difluoroborylbis(diphenylglyoximato)nickel(II), [Ni(dpgBF2)2], is described. To achieve the degradation the nickel complexes were reduced by using electrochemical means. The chemical catalysis was studied using cyclic voltammetry by monitoring currents increases as the concentration of hexachloroethane was increase in solution. The rate constant of the dehalogenation process was estimated using foot-of-the-wave analysis (FOWA), obtaining: [Ni(dmgH)2] 6.58 x 104; [Ni(dpgH)2] 6.74 x 104; [Ni(dmgBF2)2] 7.06 x 104 and [Ni(dpgBF2)2] 1.08 x 104.